1992
DOI: 10.1139/v92-202
|View full text |Cite
|
Sign up to set email alerts
|

A model of nonelectrolytic behaviour: activity coefficients

Abstract: A model is presented for binary mixtures of nonelectrolytes that reproduces successfully the activity coefficient (γi, γj, xi) data for even those (I + j) mixtures that are known to be characterized by the presence of 1:1 or 1:1 and 1:2 molecular complexes or have components that differ appreciably in their molar volumes when only limited [Formula: see text] or [Formula: see text] or [Formula: see text] data are available).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Analysis of degrees of dissociation (˛1 and 2 ) of CuCl 2 and (CuCl) + revealed that˛1 was greater than˛2 at both temperatures except in DMF at 303.15 K, where˛2 had exceptionally higher value than˛1 (Table 1). And also˛1 and˛2 kept on decreasing with increase of electrolyte concentration in all the solvents except for DMF at 303.15 K. This exceptional behavior of having relatively high values of K 2 and˛2 could be responsible for some positive EMF values of CuCl 2 in DMF at 303.15 K [22]. In this case dissociation of (CuCl) + is predicted more than CuCl 2 and thus cation-solvent interactions changed unusually, whereas in case of W and FD, both Cu(II) and (CuCl) + states were in equilibrium but (CuCl) + state dominated slightly.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…Analysis of degrees of dissociation (˛1 and 2 ) of CuCl 2 and (CuCl) + revealed that˛1 was greater than˛2 at both temperatures except in DMF at 303.15 K, where˛2 had exceptionally higher value than˛1 (Table 1). And also˛1 and˛2 kept on decreasing with increase of electrolyte concentration in all the solvents except for DMF at 303.15 K. This exceptional behavior of having relatively high values of K 2 and˛2 could be responsible for some positive EMF values of CuCl 2 in DMF at 303.15 K [22]. In this case dissociation of (CuCl) + is predicted more than CuCl 2 and thus cation-solvent interactions changed unusually, whereas in case of W and FD, both Cu(II) and (CuCl) + states were in equilibrium but (CuCl) + state dominated slightly.…”
Section: Resultsmentioning
confidence: 87%
“…Dissociation constants (K 1 , K 2 ) of CuCl 2 and (CuCl) + had equal values (0.01) at both temperatures in all the three solvents, predicting the existence of two species in equilibrium except that CuCl 2 in DMF at 303.15 K had very small values of K 1 = 0.00005 and K 2 = 0.0005 [22]. Analysis of degrees of dissociation (˛1 and 2 ) of CuCl 2 and (CuCl) + revealed that˛1 was greater than˛2 at both temperatures except in DMF at 303.15 K, where˛2 had exceptionally higher value than˛1 (Table 1).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The activity coefficient, γ 1 , of component 1 in a (1 + 2) binary mixture is a measure of molecular interactions between the components 1 and 2 and directly depends upon the effective surface fraction, S 2 , of 2 that comes into unlike contact. At the same time, thermal energy would influence the magnitude of unlike interaction energy so that γ 1 varies as some function of (χ 12 ** / RT ) S 2 , where χ 12 ** is the interaction energy.…”
Section: Graph Theory and Resultsmentioning
confidence: 99%